1995
DOI: 10.1172/jci117959
|View full text |Cite
|
Sign up to set email alerts
|

Role of hyperbilirubinemia in the impairment of osteoblast proliferation associated with cholestatic jaundice.

Abstract: Because the osteoporosis occurring in chronic cholestatic liver disease (CCLD) is associated with decreased bone formation and is reversible by liver transplantation, substances retained in plasma during cholestasis may impair osteoblast function. This hypothesis was tested using a new bioassay that measures plasma mitogenic activity (PMA) for normal human osteoblast-like (hOB) cells. In 29 jaundiced patients, mean PMA was 56.4% (P < 0.001) of that in 29 age-and sex-matched normal subjects, and the decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(104 citation statements)
references
References 27 publications
3
97
0
4
Order By: Relevance
“…These data contrast with in vitro studies demonstrating that serum with hyperbilirubinemia reduced the mitogenic activity of osteoblast-like cells (5). Some clinical studies also showed that osteoporosis is more frequent in cholestatic patients than in non-cholestatic patients with liver disease (18)(19)(20).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These data contrast with in vitro studies demonstrating that serum with hyperbilirubinemia reduced the mitogenic activity of osteoblast-like cells (5). Some clinical studies also showed that osteoporosis is more frequent in cholestatic patients than in non-cholestatic patients with liver disease (18)(19)(20).…”
Section: Discussionmentioning
confidence: 69%
“…The most relevant factors are nutritional changes, hormonal disorders and the metabolic environment inherent to the progressive deterioration of liver function (1)(2)(3)(4). Regarding this last factor, cholestasis is used as a specific indicator determining bone involvement in chronic liver disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, IMCL can also be increased between IHL and BMD in postmenopausal women with nonalcoholic fatty liver disease (9). Potential mechanisms for low BMD in patients with chronic liver disease include decreased levels of insulin-like growth factor 1 (25) and detrimental effects of bilirubin level on osteoblast proliferation (26). In our healthy obese subjects without a history of liver disease, IHL were positively associated with bone marrow fat, even after adjusting for BMI, age, and IR, suggesting that IHL may be involved regression model and IHL, IMCL, triglyceride levels, and BMI were entered as independent variables, serum triglyceride levels were significant predictors of bone marrow fat.…”
Section: Predictors Of Bone Marrow Fatmentioning
confidence: 99%
“…Bilirubin inhibits osteoblast proliferation 19 and stimulates apoptosis in rat brain neurons, 20 -23 astrocytes, 24 fibroblasts 24 and bovine brain endothelial cells. 25 However, many studies of bilirubininduced apoptosis have been conducted at high molar ratios of bilirubin to albumin or under serum-free conditions.…”
mentioning
confidence: 99%